Correlation between learning styles and student learning outcomes in Islamic religious education subjects - Santi, Santi; Supriadi, Gito; Anshari, Muhammad Redha (Univeritas Papua, 2025)
Learning outcomes are proof of the success of students in undergoing the learning process and are proof of success for teachers in educating their students. The compatibility between the learning style and the learning outcomes to be achieved will affect the learning outcomes. This study aims to examine the correlation of learning styles to student learning outcomes in Islamic religious education (PAI) subjects at Palangka Raya High School. This study involved 176 grade XI students consisting of 12 classes as a sample. Data was collected through a learning style questionnaire consisting of 30 statement items and a multiple-choice learning outcome test administered through Google Forms. The results of Spearman's correlation analysis demonstrated that the correlation coefficient between learning style and learning outcomes was 0.055 with a p-value of 0.466, which stated that there was no significant relationship between the two variables based on the analysis conducted. Thus, the student's learning style did not significantly affect the learning outcomes in PAI subjects. This study suggests looking at other more effective factors that influence learning outcomes, such as teaching methods and learning conditions, to be considered in further studies to obtain a more comprehensive picture of the factors that play a role in improving learning outcomes.